26. Factors Associated with Meningococcal Vaccination among Patients with Newly Diagnosed High-Risk Conditions. (31st December 2020) - Ghaswalla, Parinaz; Bengtson, Lindsay; Marshall, Gary S; Buikema, Ami R; Bancroft, Tim; Schladweiler, Krista; Koep, Eleena; Novy, Patricia; Hogea, Cosmina
Abstract: Background: Vaccination is recommended for persons at increased risk for invasive meningococcal disease (IMD) due to complement component deficiency (CD), asplenia or human immunodeficiency virus (HIV) infection. However, uptake of quadrivalent conjugate and polysaccharide meningococcal vaccines (MenACWY) one year following a new high-risk diagnosis is very low (doi:10.1093/ofid/ofz360.2403). This retrospective cohort study identified factors associated with MenACWY vaccination among patients newly diagnosed with CD or HIV. Methods: Patients identified from a large US commercial administrative claims database (Optum Research Database) with continuous enrollment for ≥12 months before and ≥6 months after appearance of an incident high-risk diagnosis through the end of the study period (3/31/2018) were considered eligible (Figure). Cox proportional hazards regression models were used to identify characteristics associated with time to receipt of ≥1 dose of MenACWY during time periods corresponding with Advisory Committee on Immunization Practices (ACIP) recommendations. Results: The CD cohort consisted of 1, 470 (mean=40.9 years of age) patients and the HIV cohort of 1, 208 (38.8 years). Only 7.9% and 20.8% of patients with CD or HIV, respectively, received ≥1 dose of MenACWY between their index date and the end of the study period. A strong association between receipt of MenACWY and pneumococcal vaccines was seen for CD [hazard ratio (HR): 3.2; 95% CI: 1.8–5.7] and HIV [23.0; 13.9–38.1]. Age (11–18 years; for CD only) and having a well-care visit after the index date (for CD and HIV) was associated with higher likelihood of vaccination. Vaccination rates for HIV were lowest in the South. Conclusion: The association of MenACWY vaccination with age in patients with CD suggests confusion between routine age-based and high-risk recommendations, whereas in patients with CD or HIV, the association with pneumococcal vaccines suggests that providers recognize the overlap in risk factors for IMD and pneumococcal disease. Ensuring healthcare access for these vulnerable patients and educating providers about high-risk recommendations is crucial. Funding: GlaxoSmithKline Biologicals SA (study identifier: HO-18-19581) Disclosures: Parinaz Ghaswalla, PhD, ORCID: 0000-0002-2883-5590, GlaxoSmithKline (Employee, Shareholder) Lindsay Bengtson, PhD, MPH, Optum (Employee, I am an employee of Optum. Optum was paid by GSK for this work. My employment at Optum is not contingent upon this work.) Gary S. Marshall, MD, GlaxoSmithKline (Consultant, Scientific Research Study Investigator)Merck (Consultant, Scientific Research Study Investigator)Pfizer (Consultant, Scientific Research Study Investigator)Sanofi Pasteur (Consultant, Grant/Research Support, Scientific Research Study Investigator, Honorarium for conference lecture)Seqirus (Consultant, Scientific Research Study Investigator) Ami R. Buikema, MPH, Optum (Employee, I am an employee of Optum. Optum was paid by GSK for this work. My employment at Optum is not contingent upon this work.) Tim Bancroft, PhD, Optum (Employee, I am an employee of Optum. Optum was paid by GSK for this work. My employment at Optum is not contingent upon this work.) Krista Schladweiler, PhD, Optum (Employee, I am an employee of Optum. Optum was paid by GSK for this work. My employment at Optum is not contingent upon this work.) Eleena Koep, MS, Optum (Employee) Patricia Novy, PhD, GSK (Employee, Shareholder) Cosmina Hogea, PhD, GlaxoSmithKline (Employee, Shareholder)